2019
DOI: 10.1097/md.0000000000016428
|View full text |Cite
|
Sign up to set email alerts
|

Circulating alarin concentrations are high in patients with type 2 diabetes and increased by glucagon-like peptide-1 receptor agonist treatment

Abstract: Context: Alarin has been reported to be relative to food intake and an increase in body weight. However, to date, no report has demonstrated the relationship between circulating alarin and diabetes in humans. Objective: The objective of this study is to gain insight into the possible role of alarin in humans. Design and methods: 164 patients with newly diagnosed type 2 diabetes mellitus (nT2DM), 112 IGT and 134 healthy subjects were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…Furthermore, the increment of circulating alarin in subjects with normal weight PCOS and women with obese PCOS subjects might be a compensatory up-regulation in vivo for counteracting the metabolic stress produced by obesity. Our alarin results are consistent with previous prediabetes and type 2 diabetes subjects studies [17].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the increment of circulating alarin in subjects with normal weight PCOS and women with obese PCOS subjects might be a compensatory up-regulation in vivo for counteracting the metabolic stress produced by obesity. Our alarin results are consistent with previous prediabetes and type 2 diabetes subjects studies [17].…”
Section: Discussionsupporting
confidence: 93%
“…It is possible that GDM may cause a leading to the increase of alarin secretion to a defensive response, which may represent ability for adaptation to IR or to maintain a normal glucose metabolism in the organism via the increase in GLUT4 content to improve insulin sensitivity [10]. This alarin results are line with previous prediabetes and type 2 diabetes subject studies and women with obese polycystic ovary syndrome (PCOS) subjects [17,37].…”
Section: Discussionsupporting
confidence: 84%
“…Also, peripheral and intracerebroventricular (ICV) injection of alarin elevated food intake and body weight and glucose uptake in skeletal muscle of diabetic rats [16]. Also, it has been recently reported that alarin level are high in patients with type 2 diabetes and elevated by glucagon-like peptide-1 receptor agonist treatment [17]. As known, there are some similarities between women developing type 2 diabetes and women with GDM [18].…”
Section: Introductionmentioning
confidence: 96%
“…Hu et al found that serum alarin level was significantly increased in patients with impaired glucose tolerance (IGT) and T2DM, indicating that circulating alarin gradually increased from pre-diabetic state to diabetic stage. 11 In this study, we found that alarin levels were elevated in both the T2DM non-obese group and the T2DM obese group. But the T2DM obesity group was significantly higher than the T2DM non-obese group, which indicated that the T2DM with obesity patients had a more significant effect on plasma alarin levels.…”
Section: Discussionmentioning
confidence: 50%